The Development of Tubular Photobioreactor for Microalgae Cultivation - Kunopagarnwong, Varit; Srinophakun, Thongchai Rohitatisha (ASEAN Journal of Chemical Engineering, 2022)
In a tubular photobioreactor, microalgae cells obscure one another (Self-shading), leading to the microalgae at the bottom of the tube getting less light. The objective of this research was to design and develop Tubular Photobioreactor with 93.5 liters for microalgae cultivation. The experiments had two steps. The first step was designing the solar receiver by inserting the fin into each tube wall as follows: 12-34, 1-2-3-4, 1234, and 13-24. Then, FLUENT software was used to simulate flow behavior inside the tube by Computational Fluid Dynamics by observing the pressure drop, the amount of energy consumption, and the swirling velocity to select the best fin-type. The best fin-type with the growth rate equation is introduced in the next step to simulate the microalgae’s growth and movement using the user-defined function technique. The comparison of a tubular photobioreactor is investigated between fin and without fin by observing biomass production. The results showed that algae’s optimum inlet velocity is 0.15 meters per second with the tubes containing fin-type 13-24. When simulating the growth behavior of microalgae, results show that the tubes without fins had lower biomass content than the 13-24 fin-type, which were 0.675 and 0.806 grams per liter, respectively, because the 13-24 fin-type will make well microalgae distribution leading to increase the light distribution too. Tubular photobioreactor fins type 13-24 had more biomass production, up to 19.4 percent.